Environmental state of an intertidal complex and anthropization in its catchment area - Marta Román Geada (Frontiers in Marine Science, 2014)
Environmental state analysis of an intertidal complex and the study of anthropization in its associated basin were done. The purpose was to amplify the knowledge of the relationship between land occupation changes and their effect on the marine environment. The study was divided in two stages. 1: The land use changes variation area from 1990 to 2006 in the catchment was quantified by getting the data of the Corine Land Cover (CLC) satellite images and processing them by geographical information system software. Statistical data (demographic and buildings) showed the human pressures in the area. 2: A core was collected at the intertidal complex, and the sediment was subjected to granulometric analysis, also the studies of organic matter percentage, ratios of stable carbon and nitrogen isotopes, total carbon and nitrogen, and trace metals were done. The provisional results of the CLC analysis showed that the most significant land use changes in the study period were the loss of forest soil and crops and the increase of infrastructures. In the upper 68 cm of the sediment, it was found that the grain size was finer at the upper parts of the core and the organic matter percentage decreased with depth, when the gravels appeared. The δ15N values were between 4,6 and 5,7‰ and the δ13C values were between -25,5 and -24,1‰. The C/N ratio had an increasing trend with depth with a maximum of 13.1 and a minimum of 10.2, and the inorganic elements analysis showed that the concentrations of lead, copper and zinc exceeded the background concentrations for contaminants established by the OSPAR commission.